Mosaic Subventricular Origins of Forebrain Oligodendrogenesis - Azim, Kasum; Berninger, Benedikt; Raineteau, Olivier (Frontiers in Neuroscience, 2016)
In the perinatal as well as the adult CNS, the subventricular zone (SVZ) of the forebrain is the largest and most active source of neural stem cells (NSCs) that generates neurons and oligodendrocytes (OLs), the myelin forming cells of the CNS. Recent advances in the field are beginning to shed light regarding SVZ heterogeneity, with the existence of spatially segregated microdomains that are intrinsically biased to generate phenotypically distinct neuronal populations. Although most research has focused on this regionalization in the context of neurogenesis, newer findings underline that this also applies for the genesis of OLs under the control of specific patterning molecules. In this mini review, we discuss the origins as well as the mechanisms that induce and maintain SVZ regionalization. These come in the flavor of specific signaling ligands and subsequent initiation of transcriptional networks that provide a basis for subdividing the SVZ into distinct lineage-specific microdomains. We further emphasize canonical Wnts and FGF2 as essential signaling pathways for the regional genesis of OL progenitors from NSCs of the dorsal SVZ. This aspect of NSC biology, which has so far received little attention, may unveil new avenues for appropriately recruiting NSCs in demyelinating diseases.